Equivalent Conditions of Generalized Convex Fuzzy Mappings - Xue Wen Liu; Dou He (The Scientific World Journal)
We obtain some equivalent conditions of (strictly) pseudoconvex and quasiconvex fuzzy mappings. These results will be useful to present some characterizations of solutions for fuzzy mathematical programming.